Evaluating lithium slag for geopolymer concrete: A review of its properties and sustainable construction applications - Khair, Sanjida; Rahman, SM Arifur; Shaikh, Faiz; Sarker, Prabir (2024)
This comprehensive review paper evaluates lithium slag (LS) as a promising precursor for geopolymer concrete, focusing on its workability, strength, durability, and microstructure. In the context of sustainable construction, LS emerges as a vital alternative to conventional cementitious materials, primarily due to the environmental concerns associated with cement production, such as substantial greenhouse gas emissions and air pollution. Geopolymer technology utilizes alkali activators and aluminosilicate-rich materials, offers a reduced environmental footprint and shows comparable performance to traditional cement-based concrete. In particular, LS has gained attention for its potential as an aluminosilicate precursor material in geopolymer concrete. This review investigated the recent advancements in LS-based geopolymers, exploring various processing techniques like mechanical activation, calcination, and chemical treatment to optimize LS geopolymerisation and enhance early strength development. The incorporation of binary/ternary aluminosilicate material is also discussed, aiming to improve crucial properties such as workability, strength, durability, and microstructure. The needs for comprehensive research into LS-based geopolymers to achieve their full potential in sustainable construction, promoting an environmentally friendly approach and contribution to a circular economy in the construction industry are highlighted.